2018
DOI: 10.3389/fphys.2018.00614
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterization of PepT1 and Ghrelin in Gastrointestinal Tract of Zebrafish: Effects of Spirulina Vegetarian Diet on the Neuroendocrine System Cells After Alimentary Stress

Abstract: Gastrointestinal function in vertebrates is influenced by stressors, such as fasting and refeeding, different types of diet and hormonal factors. The aim of this paper was to analyze the effect of a Spirulina (Arthrospira platensis) diet, a microalga known for its nutraceutical properties, on the gastrointestinal tract of zebrafish (Danio rerio) regarding expression of oligopeptide transporter 1 (PepT1) and ghrelin (GHR). Food deprivation and refeeding was investigated to elucidate expression of PepT1 and GHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 62 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…The presence of PepT1a and PepT1b in the intestine has been related to the possible variability of the natural environment where the fish live, to the nutritional input and to the peculiarities of the digestive system of the various fish species and to a variety of other challenges (reviewed in [12, 13]). In particular, in a large number of teleost fish species, zebrafish and other cyprinids included, the spatio-temporal expression of PepT1b intestinal mRNA largely varies during ontogeny, in response to nutritional states (e.g., food deprivation/re-feeding), dietary challenges, and/or environmental conditions (e.g., in freshwater/seawater adaptation), as well as under certain disease states (e.g., gut inflammation) [1422, 26, 30, 5163]. But, in the light of the most recent findings, the new view that PepT1a and PepT1b may both be expressed and operate in teleost fish models and similarly or differently respond to the various internal and external solicitations should always be taken into account (for details, see Table 4, and literature cited therein [4348, 50]).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PepT1a and PepT1b in the intestine has been related to the possible variability of the natural environment where the fish live, to the nutritional input and to the peculiarities of the digestive system of the various fish species and to a variety of other challenges (reviewed in [12, 13]). In particular, in a large number of teleost fish species, zebrafish and other cyprinids included, the spatio-temporal expression of PepT1b intestinal mRNA largely varies during ontogeny, in response to nutritional states (e.g., food deprivation/re-feeding), dietary challenges, and/or environmental conditions (e.g., in freshwater/seawater adaptation), as well as under certain disease states (e.g., gut inflammation) [1422, 26, 30, 5163]. But, in the light of the most recent findings, the new view that PepT1a and PepT1b may both be expressed and operate in teleost fish models and similarly or differently respond to the various internal and external solicitations should always be taken into account (for details, see Table 4, and literature cited therein [4348, 50]).…”
Section: Discussionmentioning
confidence: 99%
“…Marino et al, [ 21 ] highlighted increased interest in the use of natural-alternatives materials to that of frontline antibiotics and biocides, particularly where there is a trend towards producing farmed high-value fish with organic status. Cascio et al, [ 22 ] reported on the potential “game-changer” use of a microalgae (Spirulina) targeting beneficial effects in the gastrointestinal tract of Zebrafish; this has implications for potentially stimulating the breeding of animals. Such studies show the importance of Zebrafish ( Danio rerio ) assay due to the ability of Zebrafish stomach system to recognize small extracts such as mRNA and immune-priming genes.…”
Section: Introductionmentioning
confidence: 99%
“…Our study used the ZFET strategy as it was previously reported to be a fast, affordable and sensitive approach [ 11 ]; it also offers greater flexibility in terms of using multiple sample insertions to evaluate toxicological effects due to early stages of embryonic development [ 11 ] and for continuity in terms of relevance to the gastrointestinal anatomy in small intestine mammals [ 22 ]. This study reports on the use of ZFET assay for testing European G. applanatum extracts using seven different EPS-ENS concentrations that specifically addresses LC 50 , embryonic hatching delays, teratogenic defect, and heart rate response with clear microscopic images.…”
Section: Introductionmentioning
confidence: 99%
“…Today, fish nutrition and its effect to animal health is an important new field of study in the aquaculture industry (Lo Cascio et al, 2018;Marino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%